Moderne kunst : Keuze uit de verzameling van Museum Het Valkhof. - van de Schoor, Frank; Beugeling-van den Heuvel, Joke (Nijmegen : Museum Het Valkhof, 1999)
Adams, Willem ; van den Assem, Marjolijn ; Freijmuth, Alphons ; Sieger, Fred ; Sierhuis, Jan ; Terwindt, Robert ; Wolvecamp, Theo ; Brands, Eugène ; Egl, Herbert ; de Haas, Johan ; Janssen, Servie ; Meistermann, Georg ; den Ouden, Willem ; Armando ; Colton, Adam ; van Hemert, Frank ; Mulders, Marc ; Stoop, Pieter ; Vandekop, David ; Garouste, Gérard ; Hendriks, Marten ; Nijburg, Rinke ; Schmitz, Wolfgang ; de Vaal, Elizabeth ; Blom, Ansuya ; Van den Broeck, Frank ; van Eeden, Marcel ; Egberts, Otto ; Nolte, Titus ; van Oostende, Geert Jan ; van Amen, Woody ; Asselbergs, Gustave ; van Bentum, Rik ; Hermans, Benoît ; Middleton, Sam ; Rivers, Larry ; Smulders, Margriet ; Teulings, Raoul ; Tilson, Joe ; van Ballegooyen, Willem ; de Bie, Jan ; van Dijk, Cor ; van den Dobbelsteen, Jan ; Hendriks, Berend ; Martens, Karel ; Schoonhoven, Jan ; Vanderheyden, JCJ ; Berkulin, Arie ; Grosfeld, Jan ; Gubbels, Klaas ; Rooymans, Ron ; Teeken, Toon ; Tordoir, Narcisse ; Veenhuizen, Gerrit ; de Vries, Auke ; Bezemer, Frank ; Brusse, Mark ; Claassen, Johan ; Damsté, Christaan Paul ; de Haan, Wim ; van Kimmenade, Thijs ; Kuijpers, Theo ; Swinkels, Ad
boek